Comparison of Arch Widths Measurements Made on Digital and Plaster Models - Sedtasuppana, Aphiwat; Nunthayanon, Kulthida; Prasitsak, Thanit; Tanaslarak, Ratchawan; Satrawaha, Sirichom; Piyapattamin, Thosapol (Asian Health, Science and Technology Reports, 2017)
Objectives: To compare arch widths measurements made on plaster models by using digital caliper, digital models from direct intraoral scanned and indirect scanned on plaster models. Materials and Methods: Upper and lower impressions were taken from thirty volunteers with Class I normal occlusion or Class I malocclusion with mild crowding. The plaster models were made and digital vernier caliper was used to measure inter-canine width, anterior arch width and posterior arch width. Each volunteer and models were also scanned by intraoral scanner. Then, the 3Shape Ortho software was used to measure the arch widths. Intra-class correlation coefficient (ICCs) and One-way ANOVA (P<0.05) were used to assess intra-examiner reliability and validity of measurement between three groups. Result: According to the high values of ICC (0.98-1.00), intra-examiner error could be neglected. Moreover, there were no statistical significantly different of inter-canine width, anterior arch width and posterior arch width between three methods of measurements. Although, scanning on lower arch intraorally was difficult due to the tongue but our result showed that there were no statistical significant different in digital models group compared with plaster models group. Conclusion: The intraoral scanner can be used to measure arch widths with clinically acceptable accuracy and high reliability and reproducibility. In the future, it’s possible to use digital models instead of conventional plaster models due to its advantages. Further study should compare tooth size by using these methods to prove the effective of intraoral scanner.